Impactos da nota fiscal eletrônica na arrecadação do ICMS no Estado do Ceará: uma análise setorial - Barbosa, Márcia Pedrosa Cavalcante (2011)
The present study sets out this issue, in order to investigate the impacts of electronic invoice in the collection of VAT in the State of Ceará, more precisely in the pioneering activities in their use. It was intended to achieve this purpose by researching the history, legislation, the operational model and the benefits of this new tool, with a descriptive and econometric analysis of the activities of VAT collections required and not required in the periods before and after the fiscal policy. We used the methodological “difference in difference”, which results indicated that, in a general context, the binding nature of the invoice electronically provided an effect on the collection of VAT, on average, much higher than the observed in sectors that were not included in the policy. The intersection of information more efficiently by computerized means contributed such to reduce tax evasion as well as to improve a control over the movement of goods and services that culminated in a result of effective policy. It is noteworthy that there are other variables that affect the level of collection of VAT. However, their unavailability aggregated by the sector made it impossible to insert them in the model. So what can be said in this work is that eletronic invoice promoted a positive impact on the collection of VAT and that politics is only partly responsible for the observed growth.